2006
DOI: 10.1038/sj.ejcn.1602525
|View full text |Cite
|
Sign up to set email alerts
|

Arabinoxylan consumption decreases postprandial serum glucose, serum insulin and plasma total ghrelin response in subjects with impaired glucose tolerance

Abstract: Objective: Arabinoxylan (AX) consumption is associated with metabolic improvement during diabetes and with modulation of ghrelin, an orexigenic gut hormone. The effect of AX consumption on ghrelin secretion in disturbed metabolic states is unknown. Therefore, we investigated the postprandial responses to AX consumption of serum glucose, insulin and triglycerides and plasma total and acylated ghrelin in subjects with impaired glucose tolerance (IGT). Design: Randomized, single-blind, controlled, crossover inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(112 citation statements)
references
References 49 publications
3
104
0
3
Order By: Relevance
“…↓ glucose response area after the meal Bread containing 0, 6 or 12 g of AX 3 breakfasts on 3 days ↓ postprandial glycaemia, improvement in the insulin response [104] 15 individuals with type 2 diabetes; randomised crossover intervention Bread and muffins containing 14% AX for 5 weeks ↓ fasting glycaemia, ↓ glycaemia and insulinaemia 2 h post OGTT [105] 11 individuals with impaired glucose tolerance; single-blind, controlled, crossover intervention over 18 weeks 15 g AX supplied daily via bread and powder for 6 weeks, followed by a 6 week washout period ↓ fasting glycaemia, = insulin, After LMCT: ↓postprandial glycaemia, ↓ insulin [106,107] 15 healthy individuals; crossover intervention GIP, glucose-dependent insulinotropic polypeptide; LMCT, liquid meal challenge test; MCP-1; monocyte chemoattractant protein-1; = means no significant changes vs controls…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 99%
“…↓ glucose response area after the meal Bread containing 0, 6 or 12 g of AX 3 breakfasts on 3 days ↓ postprandial glycaemia, improvement in the insulin response [104] 15 individuals with type 2 diabetes; randomised crossover intervention Bread and muffins containing 14% AX for 5 weeks ↓ fasting glycaemia, ↓ glycaemia and insulinaemia 2 h post OGTT [105] 11 individuals with impaired glucose tolerance; single-blind, controlled, crossover intervention over 18 weeks 15 g AX supplied daily via bread and powder for 6 weeks, followed by a 6 week washout period ↓ fasting glycaemia, = insulin, After LMCT: ↓postprandial glycaemia, ↓ insulin [106,107] 15 healthy individuals; crossover intervention GIP, glucose-dependent insulinotropic polypeptide; LMCT, liquid meal challenge test; MCP-1; monocyte chemoattractant protein-1; = means no significant changes vs controls…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 99%
“…Effects on the hunger-related hormone ghrelin have been studied in response to wheat arabinoxylan intake. When 15 g/day of wheat arabinoxylan was consumed during a 6-wks period by participants with impaired glucose tolerance (n=15), total plasma ghrelin concentrations (4 h postprandial) were lowered in response to a standardised test meal by the end of the period (Garcia et al, 2007). Contradictory results were found after consumption of a wheat arabinoxylan-enriched (6 g) breakfast meal (Möhlig et al, 2005).…”
Section: Arabinoxylanmentioning
confidence: 98%
“…Eleven randomised controlled trials were identified that presented evidence on isolated gums and gelling agents in relation to energy intake (Tredger et al, 1991;Haskell et al, 1992;Pasman et al, 1997b;Panlasigui et al, 2003;Marett & Slavin, 2004;Schwab et al, 2006;Garcia et al, 2007;Mattes, 2007;Pelkman et al, 2007;Wood et al, 2007;Paxman et al, 2008), seven of which were included in a meta-analysis (Tredger et al, 1991;Pasman et al, 1997b;Schwab et al, 2006;Garcia et al, 2007;Pelkman et al, 2007;Wood et al, 2007;Paxman et al, 2008). Four trials could not be included in metaanalysis but demonstrated no statistically significant effect of soluble fibre isolates on energy intake (Haskell et al, 1992;Panlasigui et al, 2003;Marett & Slavin, 2004;Mattes, 2007).…”
Section: Energy Intakementioning
confidence: 99%
“…Nine randomised controlled trials were identified that presented evidence on isolated gums and gelling agents in relation to fasting blood glucose (Bell et al, 1990;Ryle et al, 1990;Landin et al, 1992;Pasman et al, 1997a;Marett & Slavin, 2004;Lehtimaki et al, 2005;Schwab et al, 2006;Wood et al, 2007;Garcia et al, 2007), eight of which were included in a meta-analysis (Bell et al, 1990;Ryle et al, 1990;Landin et al, 1992;Marett & Slavin, 2004;Lehtimaki et al, 2005;Schwab et al, 2006;Wood et al, 2007;Garcia et al, 2007). One trial could not be included in meta-analysis as it did not report the necessary data, but demonstrated no significant effect of soluble fibre isolates in relation to fasting blood glucose (Pasman et al, 1997a Fasting blood insulin A5.30.…”
Section: Eating Motivationmentioning
confidence: 99%
See 1 more Smart Citation